A typology of community garden in terms of location and shape in urban spaces - Dudzińska - Jarmolińska, Agnieszka (Bulletin of Geography. Socio-economic Series, 2025)
The aim of this paper is to present the author’s spatial typology of community gardens by defining their spatial characteristics, forms of development, and socio-cultural context. The typology was developed based on field research conducted in three U.S. cities and three European cities. As a result, it was determined that community gardens can be classified into six distinct spatial types.